Effect of granite industry waste addition on durability properties of fly ash blended self-compacting concrete. (18th July 2022) - Jain, Abhishek; Choudhary, Sumit; Gupta, Rajesh; Chaudhary, Sandeep; Gautam, Lilesh
Highlights: Compressive strength and durability properties of fly ash blended self compacting concrete (SCC) incorporating granite powder (GP) was evaluated. Resistance against chloride, drying shrinkage, carbonation and corrosion improved on incorporating of GP in blended SCC. GP could be positively used up to 50% as a fine aggregate substitution in eco-friendly production of blended SCC. Abstract: The continuous production of granite powder (GP) waste causes a deadly impact on environment and human life. This present study thus examines the impact of granite powder (GP) as substitute to natural fine aggregate (up to 60%) on compressive strength and durability properties of eco-friendly fly ash blended self-compacting concrete (SCC). Results revealed that strength enhanced on incorporation of up to 40% GP in concrete mixture than fly ash blended control mixture. Resistance against chloride, carbonation and corrosion improved for incorporation of up to 50% GP in concrete mixture than fly ash blended control mixture. Moreover, all the blended SCC mixtures, except SCC mixture containing 50% and 60% GP, showed higher compressive strength than ordinary Portland cement (OPC) based control SCC mixture at higher days of curing. Besides, all the blended SCC mixtures, except mixture containing 60% GP, showed better resistance against chloride, carbonation, drying shrinkage and corrosion than OPC based control SCC mixture. It was hence concluded that GP up to 50% as an alternative of fine aggregate could be positively incorporated in the production of eco-friendly fly ash blended SCC for the improvement of aforesaid durability properties (with little higher precaution against drying shrinkage).